Modeling Cell Communication in Cancer With Organoids: Making the Complex Simple - Fiorini, Elena; Veghini, Lisa; Corbo, Vincenzo (Frontiers in Cell and Developmental Biology, 2020)
Homotypic and heterotypic interactions between cells are of crucial importance in multicellular organisms for the maintenance of physiological functions. Accordingly, changes in cell-to-cell communication contribute significantly to tumor development. Cancer cells engage the different components of the tumor microenvironment (TME) to support malignant proliferation, escape immune control, and favor metastatic spreading. The interaction between cancerous and non-cancerous cell types within tumors occurs in many ways, including physical contact and paracrine signaling. Furthermore, local and long-range transfer of biologically active molecules (e.g., DNA, RNA, and proteins) can be mediated by small extracellular vesicles and this has been shown to influence many aspects of tumor progression. As it stands, there is a critical need for suitable experimental systems that enable modelling the cell-to-cell communications occurring in cancer. Given their intrinsic complexity, animal models represent the ideal system to study cell-to-cell interaction between different cell types; however, they might make difficult to assess individual contribution to a given phenotype. On the other hand, simplest experimental models (i.e., in vitro culture systems) might be of great use when weighing individual contributions to a given phenomenon, yet it is imperative that they share a considerable number of features with human cancer. Of the many culture systems available to the scientific community, patient-derived organoids already proved to faithfully recapitulate many of the traits of patients’ disease, including genetic heterogeneity and response to therapy. The organoid technology offers several advantages over conventional monolayer cell cultures, including the preservation of the topology of cell-to-cell and cell-to-matrix interactions as observed in vivo. Several studies have shown that organoid cultures can be successfully used to study interaction between cancer cells and cellular components of the TME. Here, we discuss the potential of using organoids to model the interplay between cancer and non-cancer cells in order to unveil biological mechanisms involved in cancers initiation and progression, which might ultimately lead to the identification of novel intervention strategy for those diseases.